2021
DOI: 10.14814/phy2.15121
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Lamin A/C at serine 22 modulates Na v 1.5 function

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Some kinases, such as Cdk1 and PCK, can also phosphorylate lamins in the interphase; a few sites are reported as mitotic sites, such as Ser22 and Ser392, but with a much lower rate than mitosis. A new study reported that Ser22 phosphorylation of lamin A/C could modulate the cardiac sodium channel, associated with cardiac conduction disease ( Olaopa et al, 2021 ). Another research demonstrated that lamin C was more strongly phosphorylated at Ser22 than lamin A in interphase fibroblasts ( Kolb et al, 2011 ); the reason might be that lamin C was easy to be touched by kinase due to its proximity to the nuclear interior ( Kolb et al, 2011 ).…”
Section: Phosphorylation: Multifunctional Post-translational Modifica...mentioning
confidence: 99%
“…Some kinases, such as Cdk1 and PCK, can also phosphorylate lamins in the interphase; a few sites are reported as mitotic sites, such as Ser22 and Ser392, but with a much lower rate than mitosis. A new study reported that Ser22 phosphorylation of lamin A/C could modulate the cardiac sodium channel, associated with cardiac conduction disease ( Olaopa et al, 2021 ). Another research demonstrated that lamin C was more strongly phosphorylated at Ser22 than lamin A in interphase fibroblasts ( Kolb et al, 2011 ); the reason might be that lamin C was easy to be touched by kinase due to its proximity to the nuclear interior ( Kolb et al, 2011 ).…”
Section: Phosphorylation: Multifunctional Post-translational Modifica...mentioning
confidence: 99%
“…Genes encoding for eukaryotic translation initiation and tRNA charging were also perturbed in the mutant scenario suggesting alteration in protein production machinery and kinetics. Moreover, genes associated with cell–cell adhesion, cell–matrix adhesion, and voltage gated ion channels were found to be dysregulated which were also previously reported to cause DCM presumably through disturbed mechanotransduction phenomenon (El‐Battrawy et al., 2018; Asatryan, 2019; Molina‐Navarro et al., 2013; Olaopa et al., 2021). We further validated by qRTPCR the differential expression of genes from the interleukin‐ and chemokine‐mediated signaling pathways, such as NOS2 (nitric oxide synthase 2), FAS (TNF receptor superfamily member 6), CXCL5 (chemokine with C‐X‐C motif ligand 5), IFI206 (interferon activated gene 206), MPEG1 (macrophage expressed gene 1), IL6 (interleukin 6), TNFRSF9 (tumor necrosis factor receptor superfamily, member 9), CXCL1 (chemokine of C‐X‐C motif ligand 1), CCL11 (chemokine of C‐C motif ligand 11) (Figure 4a).…”
Section: Resultsmentioning
confidence: 64%
“…Reduced stiffness dephosphorylates lamin-A/C at Ser22, which mediates lamina signaling (Buxboim et al, 2014;Virtanen et al, 2023) and differential expression of lamin-A/C as an extracellular matrix-dependent mechanosensor protein has also been suggested (Ovsiannikova et al, 2021;Urciuoli et al, 2021). More recently, phosphorylation of lamin-A/C at Ser22 modulates voltage-gated Na V 1.5 channel activity (Olaopa et al, 2021). These results may provide the potent role of lamin on the transitional pattern of adhesion to suspension.…”
Section: Various Modulating Factors and Effector Signals On Lamin-a/c...mentioning
confidence: 97%